Bringing Race to the Classroom: How a Multilingual Speaker Performs Infra Politics to Confront Raciolinguistic Ideologies - Setiono Sugiharto (EDULANGUE, 2022)
The notion of (anti) racism in applied linguistics in general and in language education in particular has gained considerable attention by scholars in the fields. Contesting the dominance of monolingualism in language education, applied linguists and language education scholars have become eager to resuscitate this notion, often implicitly averring that racism has long been insidiously penetrating in the field and surreptitiously operating under the so-called raciolinguistic ideologies. It is these ideologies that are alleged to perpetuate, and even to further the hegemony of White supremacy and empire, eventually giving rise to racial inequalities and racial hierarchies in language education. The antiracism movement, it has been asserted, needs to be enacted. This article will argue that the fervent pronouncements of raciolinguistic ideologies need to be taken seriously, so as to promote linguistic justice and linguistic equality in language education. It will first discuss the claims of raciolinguistic ideologies, and then provide examples (from a classroom practice) of how the so-called “racialized subjects” enact their quiescent capacity as social and political being in subverting identities in the perceived dominant language (i.e. English) as a way of doing infra politics –an instance of grassroots politics. In so doing, the article argues that the racialized subjects are not submissive language users, but are actively engaged themselves in resisting raciolinguistic ideologies